Is the risk of cancer in Australia overstated? The importance of competing mortality for estimating lifetime risk. Issue 1 (6th November 2019) - Bach, Anthea C; Lo, Kelvin SE; Pathirana, Thanya; Glasziou, Paul P; Barratt, Alexandra L; Jones, Mark A; Bell, Katy JL
Abstract: Objectives: To calculate lifetime risks of cancer diagnosis and cancer‐specific death, adjusted for competing mortality, and to compare these estimates with the corresponding risks published by the Australian Institute of Health and Welfare (AIHW). Design, setting: Analysis of publicly available annual AIHW data on age‐specific cancer incidence and mortality — for breast cancer, colorectal cancer, prostate cancer, melanoma of the skin, and lung cancer — and all‐cause mortality in Australia, 1982–2013. Outcome measures: Lifetime risks of cancer diagnosis and mortality (to age 85), adjusted for competing mortality. Results: During 1982–2013, AIHW estimates were consistently higher than our competing mortality‐adjusted estimates of lifetime risks of diagnosis and death for all five cancers. Differences between AIHW and adjusted estimates declined with time for breast cancer, prostate cancer, colorectal cancer, and lung cancer (for men only), but remained steady for lung cancer (women only) and melanoma of the skin. In 2013, the respective estimated lifetime risks of diagnosis (AIHW and adjusted) were 12.7% and 12.1% for breast cancer, 18.7% and 16.2% for prostate cancer, 9.0% and 7.0% (men) and 6.4% and 5.5% (women) for colorectal cancer, 7.5% and 6.0% (men) and 4.4% and 4.0% (women) for melanoma of the skin, and 7.6% and 5.8% (men) and 4.5% and 3.9% (women) for lung cancer. Conclusion: The method employed in Australia to calculate the lifetime risks of cancer diagnosis and mortality overestimates these risks, especially for men.